Epidemiology, clinical characteristics, resistance, and treatment of infections by Candida auris - Andrea Cortegiani (Journal of Intensive Care, 2018)
Abstract Candida spp. infections are a major cause of morbidity and mortality in critically ill patients. Candida auris is an emerging multi-drug-resistant fungus that is rapidly spreading worldwide. Since the first reports in 2009, many isolates across five continents have been identified as agents of hospital-associated infections. Independent and simultaneous outbreaks of C. auris are becoming a major concern for healthcare and scientific community. Moreover, laboratory misidentification and multi-drug-resistant profiles, rarely observed for other non-albicans Candida species, result in difficult eradication and frequent therapeutic failures of C. auris infections. The aim of this review was to provide an updated and comprehensive report of the global spread of C. auris, focusing on clinical and microbiological characteristics, mechanisms of virulence and antifungal resistance, and efficacy of available control, preventive, and therapeutic strategies.